O usuário idoso e as interfaces de autoatendimento bancário: estudo de caso com um banco brasileiro - CASTRO, Erika Veras de (2017)
There is currently a great concern with the aging population, as there is a striking present aspect, which is the lack of perception of the elderly in society and the consequent indifference to their hindrances and restrictions. Amongst these various hindrances, one that grows the most with the advancement of technology is the one pertaining to the interaction with the interfaces of several types of devices; in particular in self-service ATMs, whose interfacial elements somehow do not satisfy the elderly user during their operations. The main objective of this research is to analyze the interactive aspects of a self-service ATM interface of a Brazilian bank, considering the perception of elderly individuals in the city of São Luís, Maranhão. To evaluate the interaction, the proposed methodology to be carried out was based on the participative design approach and was divided in three situations, these being the initial exploration, the discovery process and the prototyping. In order to achieve results, techniques such as questionnaires, focus groups and usability tests were employed using a paper prototype with the purpose of validating the suggested hypothesis, and thus results and requirements were generated for the adequacy of elements present in these interfaces. The main results achieved were the identification of the main executed tasks, which are withdrawal and balance consultation. Another result was the identification of the main interactive difficulties, in which it was observed that the biggest one was the short time of the transition of the screens, and, through the test with the prototype, it was detected that the placements of some items are not satisfactory for the users.